Environmental risk assessment of genetically modified organisms. (CABI, 2008)
This book (13 chapters), the fourth in a series (the first, second and third books focused on Bt maize in Kenya, Bt cotton in Brazil, and risk assessment and management of transgenic fish, respectively) that provides scientifically peer-reviewed tools that can help developing countries strengthen their own scientific and technical capacity in biosafety of genetically modified organisms (GMOs), focuses on the potential environmental effects of Bt cotton in Vietnam within a broader context of setting procedures and methods for regulating the introduction of GM crops. The environmental effects considered are those on nontarget organisms, gene flow to cotton relatives, and the evolution of resistance in the target pests. Processes for evaluating the potential benefits of GM plants in Vietnam and the necessary requirements for characterizing transgenes and transgenic traits are covered. This book will be used as a technical manual to enable Vietnamese scientists to evaluate the potential environmental impacts of Bt cotton prior to commercialization. This publication will also equip governments, scientists, potential users of GMOs, and civil society organizations in Vietnam and other countries with knowledge on methods that are available for conducting environmental risk assessments of GMOs.